Evaluating the Harvest Rate Recommendation for Northern Bobwhites in South Texas - D. Abraham Woodard; Leonard A Brennan; Fidel Hernández; Humberto L Perotto-Baldivieso; Neal Wilkins; Andrea Montalvo (National Quail Symposium Proceedings, 2022)
The current harvest rate recommendation for northern bobwhites (Colinus virginianus; hereafter, bobwhite) in South Texas, USA is 20% of the autumn population, including crippling loss. This recommendation is based on population simulations of empirical data. We completed the first field evaluation of the 20% harvest recommendation by comparing prehunting and posthunting bobwhite density estimates on a hunted and nonhunted site in South Texas during the 2018–2019, 2019–2020, and 2020–2021 statewide bobwhite hunting seasons in Jim Hogg County, Texas. We conducted line-transect distance sampling surveys on 4 occasions per year (early November, mid-December, late January, early March) from a helicopter platform and prescribed the 20% annual bobwhite harvest from the November density estimate. According to our bobwhite density estimates, we found that bobwhite mortality (e.g., population decline) varied seasonally between hunted ( = 54% ± 3%) and nonhunted sites ( = 46% ± 5%). Our spring density estimates on both sites (i.e., hunted vs. nonhunted) were similar through the first 2 years but diverged in 2020–2021, with bobwhite densities that were 129% higher on the nonhunted site. Comparing our annual spring density results to the means reported from population models (i.e., 100-year simulations) used to create the 20% harvest recommendation, we found that the mean spring density of the model simulations was higher than our mean field estimates on both our hunted (+59%) and nonhunted sites (+77%). We recommend a conservative approach to prescribing a bobwhite harvest in South Texas, such as using the lower 95% confidence interval of a bobwhite abundance estimate for calculating harvest prescriptions, due to variability within density estimates and bobwhite survival in semiarid ranges.
Keywords: bobwhite hunting; Colinus virginianus; harvest rate recommendations; northern bobwhite; sustainable quail harvest.